From the workshop to the workplace: Relocating faculty development in postgraduate medical education. (3rd June 2018) - Morris, Clare; Swanwick, Tim
Abstract: Introduction: Postgraduate medical education takes place almost entirely in the clinical workplace, supported by healthcare professionals who strive to combine service and educational roles. Over the past decade, we have witnessed the emergence and growth of new forms of educational activity within postgraduate medical education. Under the umbrella term of "faculty development", these activities move beyond a narrow emphasis on "teaching the teachers to teach" to a wide range of interventions focused on enhancing educational climate, educational infrastructure and educational practices within and across healthcare organizations. Method: Drawing on key developments in the UK over the last 10 years, we trace how faculty development in postgraduate medical education has evolved, illustrate the plurality of purposes, and practices currently being adopted and signal emerging trends. Discussion: We highlight that due to the location of UK medical training programs outside "the academy", innovations and developments in faculty development are largely silent in the formal medical education literature. Changing demographics, service pressures, and evolving healthcare systems continue to present serious challenges to both work-based training and learning.